The effects of defensive style and final game outcome on the external training load of professional basketball players - Castillo, Daniel; Raya-González, Javier; Clemente, Filipe; Conte, Daniele; Rodríguez-Fernández, Alejandro (Biology of Sport, 2021)
This study aimed to analyse the influence of different contextual factors (i.e., defensive style and game outcome) on basketball players’ external load during games-based drills using ultrawideband (UWB) technology. Fourteen male professional basketball players belonging to an elite reserve Spanish club (ACB) participated in this study. The games-based drills consisted of one bout of 10 min played 5vs5 in which players were instructed to use man-to-man defence (MMD) and/or zone defence (ZD). In addition, the final game outcome (i.e., winning or losing) of the game-based drill was registered. External load variables per minute were recorded: total distance covered, distance covered in different speed zones, distance covered while accelerating and decelerating, maximum speed, steps, jumps and player load. A two-way ANOVA with the Tukey post hoc test was used to assess the impact of defensive style and final game outcome and the interaction of both factors on the external load encountered by basketball players. No meaningful differences (unclear) were found in the external loads between playing with MMD and with ZD and between winning and losing teams except for greater distance at high-speed running (18.0–24.0 km·h-1) in winning teams (p -2 m·s-2) (p = 0.041; ES = 0.70) and jumps (p = 0.037; ES = 0.68). These results could potentially help coaching staff in prescribing an appropriate workload during basketball-specific gamebased drills, and ultimately enhance the match performance.